Peran Green Product Innovation Dalam Memediasi Pengaruh Corporate Social Responsibility Terhadap Kinerja Bisnis Industri Kreatif: The Role of Green Product Innovation in Mediating the Effect of Corporate Social Responsibility on the Business Performance of Creative Industries - Hadiah Fitriyah; Bambang Tjahjadi; Noorlailie Soewarno (Journal of Accounting Science, 2020)
This study aims to empirically examine the role of green product innovation in mediating the influence of corporate social responsibility on the business performance of the creative industries of batik. The research approach used is quantitative research. The population is the creative industries of spread the r Sidoarjo and Bangkalan regions. The number of Small and Medium Industries of batik crafts in Sidoarjo and Bangkalan is 98 batik creative industries. The sample in this study were 79 creative industries of batik using the Slovin formula, then the determination and distribution of the sample was based on simple random sampling. The analytical method used in the data processing in this study uses SEM-PLS with the help of SmartPLS software. The results showed that: (1) corporate social responsibility (CSR) influences green product innovation (GPI) with a t value of 5.384 and a Pvalue of 0.000; (2) green product innovation (GPI) influences business performance with a t value of 5.492 and Pvalue of 0.000; (3) green product innovation(GPI) is able to mediate the influence of corporate social responsibility (CSR) business performance (BP) of creative industries with a t value of 3.771 and a Pvalue of 0.000.